A STATISTICAL APPROACH TO ADAPTIVE PARAMETER TUNING IN NATURE-INSPIRED OPTIMIZATION AND OPTIMAL SEQUENTIAL DESIGN OF DOSE-FINDING TRIALS - Choi, Kwok Pui (Academia Sinica, 2021)
10.5705/ss.202020.0412